Find the general solutions of the following equations.
LINEAR DE
BERNOULLI'S EQUATION
Solution.
All equations will be done by the method of variation of a constant.
1.1
1) "\\frac{dx}{dy}-\\frac{4x}{y}=0"
"\\frac{dx}{x}=\\frac{4dy}{y}"
"\\int\\frac{dx}{x}=\\int\\frac{4dy}{y}"
"x=Cy^4,"
where C is some constant.
2) Let be "x=C(y)y^4,"
then"x'=C'(y)y^4+4C(y)y^3."
We will have
"C'y^4+4Cy^3-\\frac{4}{y}Cy^4=y^5."
From here "C'(y)=y."
So, "C(y)=\\frac{y^2}{2}."
And, "x=\\frac{y^2}{2}y^4=\\frac{y^6}{2}."
3)
"x=Cy^4+\\frac{y^6}{2}."1.2
1) "\\frac{dy}{dx}+\\frac{y}{x}=0"
"\\frac{dy}{y}=-\\frac{dx}{x}"
"\\int\\frac{dy}{y}=-\\int\\frac{dx}{x}"
"yx=C"
"y=\\frac{C}{x},"
where C is some constant.
2) Let be "y=\\frac{C(x)}{x},"
then "y'=\\frac{C'(x)x-C(x)}{x^2}."
We will have
"\\frac{C'x-C}{x^2}+\\frac{C}{x^2}=\\cos{x}+\\frac{\\sin{x}}{x}"
From here "C'(x)=x\\cos{x}+\\sin{x}."
So, "C(x)=x\\sin{x}."
And, "y=\\frac{x\\sin{x}}{x}=\\sin{x}."
3)
"y=\\frac{C}{x}+\\sin{x}."1.3
1) "\\frac{dx}{dy}+\\frac{x(2-y)}{y}=0"
"\\frac{dx}{x}=-\\frac{2-y}{y}dy"
"\\int\\frac{dx}{x}=-\\int\\frac{2-y}{y}dy"
"x=\\frac{Ce^y}{y^2},"
where C is some constant.
2) Let be "x=\\frac{C(y)e^y}{y^2},"
then"x'=\\frac{(C'(y)e^y+C(y)e^y)y^2-C(y)e^y2y}{y^4}."
We will have
"\\frac{(C'(y)e^y+C(y)e^y)y^2-C(y)e^y2y}{y^4}+\\frac{C(y)e^y}{y^2}\\frac{2-y}{y}=\\frac{1}{y}."
From here "C'(y)=\\frac{y}{e^y}."
So, "C(y)=-\\frac{y+1}{e^y}."
And, "x=-\\frac{y+1}{y^2}."
3)
"x=C\\frac{e^y}{y^2}-\\frac{y+1}{y^2}.""2.1. \\frac{dy}{dx}-\\frac{3y}{2x}=\\frac{y^3}{2x^3}"Divide both parts of equation by "y^3."
Substitution "z=\\frac{1}{y^2}."
Then "z'+\\frac{3z}{x}=-\\frac{1}{x^3}."
1) "\\frac{dz}{dx}+\\frac{3z}{x}=0"
"\\frac{dz}{dx}=-\\frac{3z}{x}"
"\\int\\frac{dz}{dx}=-\\int\\frac{3z}{x}"
"z=\\frac{C}{x^3},"
where C is some constant.
2) Let be "z=\\frac{C(x)}{x^3},"
then "z'=\\frac{C'(x)x^3-3x^2C(x)}{x^6}."
We will have
"\\frac{C'}{x^3}-\\frac{3C}{x^4}+\\frac{3C}{x^4}=-\\frac{1}{x^3}"
From here "C'(x)=-1."
So, "C(x)=-x."
And, "z=-\\frac{1}{x^2}."
3)
"z=\\frac{C}{x^3}-\\frac{1}{x^2}."From here
2.2
Divide both parts of equation by "y^{-1}" .
Substitution "z={y^2}."
Then "z'-\\frac{z}{x}=-2{x^2}."
1) "\\frac{dz}{dx}-\\frac{z}{x}=0"
"\\frac{dz}{z}=\\frac{dx}{x}"
"\\int\\frac{dz}{dx}=-\\int\\frac{3z}{x}"
"z={C}{x},"
where C is some constant.
2) Let be "z={C(x)}{x},"
then "z'=C'(x)x+C(x)."
We will have
"{C'}{x}+C-\\frac{Cx}{x}=-2x^2."
From here "C'(x)=-2x."
So, "C(x)=-x^2."
And, "z=-{x^3}."
3)
"z={C}{x}-{x^3}."From here
2.3
Divide both parts of equation by "y^2."
Substitution "z=\\frac{1}{y}."
Then "z'-{z}=-2xe^x."
1) "\\frac{dz}{dx}-z=0"
"\\frac{dz}{z}=dx"
"\\int\\frac{dz}{z}=\\int{dx}"
"z={C}{e^x},"
where C is some constant.
2) Let be "z={C(x)}{e^x},"
then "z'={C'(x)e^x+C(x)}{e^x}."
We will have
"{C'}{e^x}+{C}{e^x}-{C}{e^x}=-2xe^x"
From here "C'(x)=-2x."
So, "C(x)=-x^2."
And, "z=-{x^2}e^x."
3)
"{C}{e^x}-{x^2}e^x."From here
Comments
Leave a comment